Fatigue crack growth behavior of beta-annealed Ti–6Al–2Sn–4Zr–xMo (x = 2, 4 and 6) alloys: Influence of microstructure and stress ratio. (February 2016) - Qiu, Jianke; Feng, Xin; Ma, Yingjie; Lei, Jiafeng; Liu, Yuyin; Huang, Aijun; Rugg, David; Yang, Rui
Highlights: Attempt to experimentally separate the effects of microstructure and stress ratio on the FCG behavior in three beta-annealed Ti alloys. Identified the most important microstructural parameter as the alpha/beta colony size which in turn depends strongly on the Mo-content. An increased stress ratio was found to reduce the roughness induced crack closure both through larger crack opening levels and through reduced crack deflection. A prominent transition on the da / dN vs. Δ K plots was observed in the extra-coarse microstructure tested under R = 0.1. Abstract: The influence of microstructures ( β grain size, α / β colony size and width of α lath) and stress ratios ( R = 0.1, 0.7) on fatigue crack growth (FCG) behavior of beta-annealed Ti624 x ( x = 2, 4 and 6) alloys was investigated. The FCG rate curves, crack paths, and the plastic zone ahead of the crack tip were compared. The reducing FCG resistance from Ti6242 to Ti6246 was found to stem from decreasing α / β colony size. Increasing stress ratio also reduced crack deflection and crack closure, and thus decreased the FCG resistance. The relevant mechanisms were discussed in terms of K max and crack closure effect.